Antioxidant use as dietary therapy in patients with multiple sclerosis - Laura González-González; Jesús Giovanni Pérez-Cortéz; Mario Flores-Aldana; Nayeli Macías-Morales; Carlos Hernández-Girón (Medwave, 2015)
INTRODUCTION Multiple sclerosis is an immune-mediated disease that produces chronic inflammation and neural degeneration. The disease progresses with acute attacks that result in myelin inflammation. This in turn increases oxidative stress and favors the appearance of reactive oxygen species. Reactive oxygen species damage neural cells causing apoptosis. The etiology of multiple sclerosis remains unknown and current therapy is aggressive and expensive. Recently, complementary and alternative medicine therapies have been proposed to control pathogenesis and symptoms of this disease. It is believed that these therapies help slow the progression of multiple sclerosis and improve survival.